Pelatihan Pembuatan Konten Yang Baik Dan Menarik Pada Media Sosial Dengan Memanfaatkan Kecerdasan Buatan (AI) Di RT 4/RW 3 Kelurahan Duri Utara Jakarta Barat - Wahyu Pramusinto; Sejati Waluyo; Ika Susanti; Ferdiansyah (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The development of artificial intelligence (AI) technology has experienced rapid growth in the last decade. AI plays a significant role not only in the industrial and academic sectors but also in the social sphere. A popular trend among young people today is becoming a content creator on social media. This social media content creator also opens up vast business opportunities, whether in the form of personal branding, endorsements, or independent product and service promotions. Becoming a content creator is no longer limited to professionals, but has become an attractive option for the younger generation due to its flexibility and promising income potential. However, being a good content creator also requires basic knowledge that young people need to have to develop their creativity. Many challenges are faced in content creation, such as limited ideas, technical skills, and consistency in presenting interesting and valuable content. Through community service training conducted by the author, by utilizing artificial intelligence (AI) to assist content creation in various aspects of content production, from scriptwriting, graphic design, to editing. It is hoped that young people in the neighborhood can recognize and utilize AI technology to become creative, positive, and competitive content creators. This activity not only encourages self-expression and creativity, but also opens up new economic opportunities.